Метафора книга природи як засіб моделювання картини світу - Лариса Кравець; Larysa Kravets; Kravec Larissza (Oficyna Wydawnicza ATUT, 2020)
Резюме. Мета цього дослідження простежити еволюцію змісту метафори книга природи впродовж її тривалого функціонування у зв’язку зі змінами картини світу.

Abstract. Metaphor "book of nature" as a means of modeling a picture of the world The purpose of the study is to trace the evolution of the content of the book of nature metaphor over its long-term functioning. The article describes the use and content of the book of nature metaphor in various cultural and historical contexts. An analogy of the world with text appears in the Middle East. In the Middle Ages, the book of nature metaphor interpreted the world as a creation of God. The Ukrainian philosopher and poet Skovoroda understood the world as a book that a person creates. In romanticism, a metaphor of the book of nature reveals the contrast between the mysterious wisdom of nature and scientific knowledge. In Ukrainian modern literature metaphor functions as a means of imagery.
Metaphor “book of nature” as a means of modeling a picture of the world
Keywords: metaphor; worldview; book of nature; metaphor model; метафора; мовна картина світу; книга природи; модель метафори